Study protocol of the Edinburgh and Lothian Virus Intervention Study in Kids: a randomised controlled trial of hypertonic saline nose drops in children with upper respiratory tract infections (ELVIS Kids). Issue 5 (5th May 2021) - Ramalingam, Sandeep; Graham, Catriona; Oatey, Katherine; Rayson, Phillip; Stoddart, Andrew; Sheikh, Aziz; Cunningham, Steve
Abstract : Introduction: Edinburgh and Lothians' Viral Intervention Study Kids is a parallel, open-label, randomised controlled trial of hypertonic saline (HS) nose drops (~2.6% sodium chloride) vs standard care in children <7 years of age with symptoms of an upper respiratory tract infection (URTI). Methods and analysis: Children are recruited prior to URTI or within 48 hours of developing URTI symptoms by advertising in areas such as local schools/nurseries, health centres/hospitals, recreational facilities, public events, workplaces, local/social media. Willing parents/guardians, of children <7 years of age will be asked to contact the research team at their local site. Children will be randomised to either a control arm (standard symptomatic care), or intervention arm (three drops/nostril of HS, at least four times a day, until 24 hours after asymptomatic or a maximum of 28 days). All participants are requested to provide a nasal swab at the start of the study (intervention arm: before HS drops) and then daily for four more days. Parent/guardian complete a validated daily diary, an end of illness diary, a satisfaction questionnaire and a wheeze questionnaire (day 28). The parent/guardian of a child in the intervention arm is taught to prepare HS nose drops. Parent/guardian of children asymptomatic at recruitment are requested to inform the research team within 48 hours of their child developing an URTI and follow the instructions already provided. The day 28 questionnaire determines if the child experienced a wheeze following illness. Participation in the study ends on day 28. Ethics and dissemination: The study has been approved by the West of Scotland Research Ethics Service (18/WS/0080). It is cosponsored by Academic and Clinical Central Office for Research and Development—a partnership between the University of Edinburgh and National Health Service Lothian Health Board. The findings will be disseminated through peer-reviewed publications, conference presentations and via the study website. Trial registration number: NCT03463694 .